Effects of coal-derived compound fertilizers on soil bacterial community structure in coal mining subsidence areas - Meng, Huisheng; Wang, Shuaibing; Zhang, Jie; Wang, Xiangying; Qiu, Chen; Hong, Jianping (Frontiers in Microbiology, 2023)
The land damaged by coal mining can be recovered to healthy condition through various reclamation methods. Fertilization is one of the effective methods to improve soil fertility and microbial activity. However, the effects of coal-derived compound fertilizers (SH) on bacterial communities in coal mining subsidence areas still remains unclear. Here, we studied the effects on the nutrient characteristics and bacterial communities in fertilizer-reclaimed soil (CK, without fertilizer; CF, common compound fertilizers; SH, coal-derived compound fertilizers) in coal mining subsidence areas and we applied SH with four different nitrogen application rates (90 kg/hm2, 135 kg/hm2, 180 kg/hm2, 225 kg/hm2). The results showed that the application of SH significantly increased the contents of available nitrogen (AN), available phosphorus (AP), available potassium (AK), total phosphorus (TP) and soil organic matter (SOM) compared with CK, as well as the bacterial richness (Chao1) and diversity (Shannon) in reclaimed soil that increased first and then decreased with the increase of nitrogen application. Under the same nitrogen application rate (135 kg/hm2), the nutrient content, Chao1 and Shannon of SH2 treatments were higher than those of CF treatment. Meanwhile, SH increased the relative abundance of Proteobacteria, Actinobacteria and Gemmatimonadetes. LEfSe analysis indicated that the taxa of Acidobacteria and Actinobacteria were significantly improved under SH treatments. In addition, it showed that SOM positively correlated (p < 0.01) with bacterial diversity in reclaimed soil. Canonical correspondence analysis (CCA) and Variance partitioning analysis (VPA) showed that SOM was the most important factor affecting the change of bacterial community structure in reclaimed soil. In conclusion, application of SH can not only increase nutrient content and bacterial diversity of reclaimed soil, but also improve bacterial community structure by increasing bacterial abundance.